Edukasi Dan Mobilisasi (ROM) pada Lansia Penderita Stroke dengan Audio Visual di Panti Jompo Welas Asih Tasikmalaya - Jajuk Kusumawaty; Adi Nurapandi (KOLABORASI JURNAL PENGABDIAN MASYARAKAT, 2022)
Introduction: Stroke is a cardiovascular disease which is globally estimated in 2030, 25 million sufferers will end up with death. Problems that usually occur in post-stroke patients are paralysis in part of the body, stiffness or weakness in muscles. One of the actions that can be taken is to increase knowledge in patients by providing education using audio-visual-based media about ROM (Range of Motion) in order to accelerate the healing process. Objective: To provide education and mobilization of ROM for  elderly with stroke using audio visuals at the Welas Asih Nursing Home in Tasikmalaya. Method:: The method in this activity is counseling, video delivery and guided practice. Participants  were 23 elderly stroke patients. This community dedication implemented on Saturday, April 03, 2021, at the Welas Asih Nursing Home in Tasikmalaya. Result: The success of this service can be seen from the enthusiasm and enthusiasm of the elderly who play an active role in evaluating the material that has been delivered. Conclussion: The implementation of service activities was carried out smoothly, all participants were committed to carrying out all the recommendations to help accelerate stroke recovery